Toshiba / Azinuddin Mohd Asri - Mohd Asri, Azinuddin (2022)
The aim of this assignment is to discover the product's flaw. The company I've picked is Toshiba Corporation, which was founded on July 11th, 1875 by Tanaka Hisashige. To conduct my research, I selected the RZE-BT 180H's headphone from their extensive product line. In this case study, I used a SWOT analysis to evaluate the RZE-BT 180H's strengths, weaknesses, opportunities, and threats. The biggest issue I found with the RZE-BT 180H is that the audio lacks clarity, in contrast to other Toshiba equipment such as their laptop speakers, Toshiba TV, wireless Bluetooth speakers, and others. The greatest remedy I can think have based on the situation is to replace the diaphragm on a pair of headphones, where the diaphragm's quality effects the overall quality of the headphone. Finally, the recommended solution for this headset would result in higher user satisfaction for individuals who chose to use the headphone. Aside from that, if it works, it will help increase revenue because demand for the headphones will definitely rise once people realize how much better they have gotten as a consequence of the proposed solution.